Presence of wall-devoid micro-organisms in hypopharyngeal glands of forager bees (Hymenoptera, Apidae) - daCruzLandim, C.; deMoraes, RLMS (Faculty Press, 1996)
The occurrence of mycoplasma-like bodies in the axial duct and intracellular canaliculli from hypopharyngeal glands of bees (Meliponinae and Apinae) is described. Since they are not found within cells and due to the absence of cellular alterations in the infected glands it is suggested that micro-organisms are not pathogenic to the bees.
Keywords: ultrastructure; micro-organisms; glands; workers; bees; Melipona; Apis